F24 Differences in companion and subject ratings of subjects' behaviour using the frontal systems behaviour scale (FrSBe)- findings from the track-hd study. (16th November 2010) - Callaghan, J; Craufurd, D; Acharya, T; Dürr, A; Leavitt, B R; Roos, R A C; Langbehn, D R; Stout, J C; Tabrizi, S J; ,
Abstract : Background: TRACK-HD is a multi-centre, longitudinal study investigating a range of motor, cognitive, neuropsychiatric and imaging measures as potential biomarkers for clinical trials in Huntington's disease (HD). The neuropsychiatric battery includes the Frontal Systems Behaviour Scale (FrSBe), a 46-item scale measuring behaviours associated with damage to the frontal lobes of the brain. In addition to subjects rating their own behaviour on the FrSBe, companions also rated subjects' behaviour. This provided an opportunity to investigate HD patients' insight into their behaviour by studying discrepancies between subject and companion ratings. Method: 225 TRACK-HD subjects (62 premanifest gene carriers far from onset, 52 near to onset, 70 stage 1 HD and 41 stage 2 HD) completed the FrSBe. In addition, 164 companions (77 of premanifest subjects and 87 of early HD subjects) rated subjects' behaviour with the FrSBe. Results: Companion ratings indicate a worsening of FrSBe scores with disease progression, especially in subjects with manifest HD. In contrast, subjects' self ratings did not show the same deterioration in FrSBe scores across the pre-HD and stage 1 subgroups, with the biggest discrepancy between subject and companion ratings at stage 1 HD. Surprisingly, self-ratings of stage 2 subjects were markedly worse than those at stage 1, almost eliminating this discrepancy between companion and self-ratings. Companion FrSBe ratings correlated more strongly with objective measures of cognitive and behavioural function than did subjects own ratings. Conclusion: The existence of a discrepancy between companion and subjects' own ratings using the FrSBe in stage 1 HD but not in those with more advanced disease suggests that denial (as a psychological defence mechanism) is a more likely explanation than a loss of insight secondary to cognitive impairment.